Trends in hip replacements between 1999 and 2012 in Sweden. Issue 1 (25th September 2017) - Cnudde, Peter; Nemes, Szilard; Bülow, Erik; Timperley, John; Malchau, Henrik; Kärrholm, Johan; Garellick, Göran; Rolfson, Ola
ABSTRACT: National Registers document changes in the circumstance, practice, and outcome of surgery with the passage of time. In the context of total hip replacement (THR), registers can help elucidate the relevant factors that affect the clinical outcome. We evaluated the evolution of factors related to patient, surgical procedure, socio‐economy, and various outcome parameters after merging databases of the Swedish Hip Arthroplasty Register, Statistics Sweden and the National Board of Health and Welfare. Data on 193, 253 THRs (164, 113 patients) operated between 1999 and 2012 were merged. We studied the evolution of surgical volume, patient demographics, socio‐economic factors, surgical factors, length‐of‐stay, mortality rate, adverse events, re‐operation and revision rates, and Patient Reported Outcome Measures (PROMs). Throughout this time period the majority of patients were operated on with a diagnosis of primary osteoarthritis. Comorbidity indices increased each year observed. The share of all‐cemented implants has dropped from 92% to 68%. More than 88% of the bearings were metal‐on‐polyethylene. Length‐of‐stay decreased by 50%. There was a reduction in 30‐ and 90‐day mortality. Re‐operation and revision rates at 2 years are decreasing. The post‐operative PROMs improved despite the observation of worse pre‐operative pain scores getting over time. The demographics of patients receiving a THR, their comorbidities, and their primary diagnosis are changing. Notwithstanding these changes, outcomes like mortality, re‐operations, revisions, and PROMs have improved. The practice of hip arthroplasty has evolved, even in a country such as Sweden that is considered to be conservative with regard taking on new surgical practices. © 2017 The Authors. Journal of Orthopaedic Research ® Published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society. J Orthop Res 36:432–442, 2018.